Bezpieczeństwo regionalne z perspektywy Pekinu - Gacek, Łukasz (Regional security from beijing’s perspective, 2009)
Beijing propagate the concrete vision of regional order. Stressing point of peaceful rise China concentrate on activities connected with changing actual social and economic structure. China need time to become a global superpower. Stability in closing neighborhood is very important in case of successful realization of the program concerned modernization of the state. The main points describing relations with neighbors, stressing principle of equal treating all countries despite of their potentials and principle of noninterference in their internal cases, allow to build positive climate around Chinese foreign policy
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 213-222